Caracterização magnética de filmes de cromo e cromocobalto preparados por eletrodeposição - Bertelli, Tiago Pulce (Universidade Federal de São Carlos, 2008)
Magnetic properties of electrodeposited of chromium and chromium-cobalt thin films on cooper substrate were investigated. The samples were prepared without introduction of additives. This procedure following to samples with granular structure. Magnetization measurements as a function of applied magnetic field and temperature show that the magnetic behavior exhibit a strong dependence on the thickness of the electrodeposited film and the samples presents a superparamagnetic behavior associated with the formation of ferromagnetism surface.
MAGNETIC CARACTERIZATION OF CHROMIUM AND CHROMIUM-COBALT FILMS PREPARED BY ELECTRODEPOSITION METHOD
Keywords: Magnetismo; Filmes de cromo; Ferromagnetismo; CIENCIAS EXATAS E DA TERRA::FISICA